Root Square Mean Labeling of Theta Related Graphs - R. Mani, S. Meena (Mathematical Statistician and Engineering Applications, 2022)
A graph with vertices and edges is called root square mean graph if it is possible to label the vertices with distinct lables from in such a way that when each edge is labeled with , then the resulting edge labels are distinct. In this case is called a root square mean labeling of In this paper we prove that theta related graphs such as are all root square mean graphs.